COMPARISON OF THE EFFECTIVENESS OF ONDANSETRON IN BREAST CANCER PATIENTS AFTER CHEMOTHERAPY FAC (Fluorouracil, Doxorubicin Cyclophosphamide) AND TC (Taxane Cyclophosphamide) - Azka Akhmad Fauzi; Titin Setyowati; Yanuarita Tursinawati; Muslimah (PT. Radja Intercontinental Publishing, 2026)
Breast cancer is one of the leading causes of morbidity and mortality in women worldwide. Chemotherapy with the regimens of FAC (Fluorouracil, Doxorubicin, Cyclophosphamide) and TC (Taxane Cyclophosphamide) is often used in the treatment of breast cancer, but side effects such as Chemotherapy-Induced Nausea and Vomiting (CINV) can impact the patient's quality of life. Ondansetron, a 5-HT3 serotonin receptor antagonist, has been widely used as an antiemetic therapy. This study aims to compare the effectiveness of Ondansetron in overcoming CINV in breast cancer patients receiving FAC and TC regimen chemotherapy. The research design used Quasi-Experimental with Two Group Pretest-Posttest, involving 36 patients selected by purposive sampling at Ken Saras Hospital in December 2024 – January 2025. Data were collected using the Rhodes Index of Nausea, Vomiting, and Retching (RINVR) and analyzed by paired-sample t-test and independent-sample t-test. The results showed that Ondansetron effectively lowered the RINVR score significantly in both groups (p = 0.00). However, there was no significant difference in the effectiveness of Ondansetron between the FAC and TC regimens, either before (p = 0.065) or after (p = 0.118) chemotherapy. The conclusions of this study showed that Ondansetron had good effectiveness in reducing CINV in both groups of patients, although there was no significant difference between the regimens.